The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00006123-199908000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosotomy with Radiosurgery

Abstract: The outcomes suggest that radiosurgical corpus callosotomy may be a promising alternative treatment to open callosotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…Erickson's work established the major role of corpus callosum as the seizure propagation pathway in the monkeys. (Pendl, Eder et al 1999) Effect of the callosotomy in the seizure generalization has also been demonstrated in animal studies. (Crowell and Ajmone Marson 1972;Marcus and Watson 1966) …”
Section: Back Ground With Historical Developmentmentioning
confidence: 87%
See 1 more Smart Citation
“…Erickson's work established the major role of corpus callosum as the seizure propagation pathway in the monkeys. (Pendl, Eder et al 1999) Effect of the callosotomy in the seizure generalization has also been demonstrated in animal studies. (Crowell and Ajmone Marson 1972;Marcus and Watson 1966) …”
Section: Back Ground With Historical Developmentmentioning
confidence: 87%
“…(Wyler 1993) Currently, endoscopic anterior callosotomy and radiosurgical callosotomy are some new approaches attempted by some investigators. (Pendl, Eder et al 1999;Tubbs, Smyth et al 2004;Eder, Feichtinger et al 2006) Along with clinical application of callosotomy, experimental data has accumulated as well over the years. Erickson's work established the major role of corpus callosum as the seizure propagation pathway in the monkeys.…”
Section: Back Ground With Historical Developmentmentioning
confidence: 99%
“…Since that time, refinements in surgical technique have reduced the initially steep morbidity and mortality of the procedure (97). As the major connective tract between the two cerebral hemispheres, the fibers of the corpus callosum play a major role in seizure generalization.…”
Section: Corpus Callosotomymentioning
confidence: 99%
“…13,17 Radiosurgical corpus callosotomy may be a promising safe and noninvasive alternative to open callosotomy. 1,4,6,19,26 This modality of treatment can be used in situations where patients have more than 2 seizure types and after a failed partial callosotomy. Small case series and individual case reports have claimed that the noninvasive nature of radiosurgery may serve to avoid transient and permanent surgical morbidity, including the disconnection syndromes, related to surgical manipulation, frontal lobe retraction, and venous injury.…”
Section: Other Surgical Alternatives and Adjunctsmentioning
confidence: 99%